Engineering geological map of the urban area of Kastoria, NW Greece - Konstantopoulou, G.; Vacondios, I. (Bulletin of the Geological Society of Greece, 2007)
In the present work, the engineering geological conditions of the urban area of Kastoria were examined. More specifically a geotechnical assessment of subsoil and rock outcrops within a minimum depth of 20 m bellow surface is made, for urban planning purposes. Landslide potential of the studied area including mainly rock falls and ground subsidence was also evaluated. Eleven engineering geological units were identified and mapped at 1:5.000 scale, which constitute the foundation ground of the old Kastoria town, as well as of its new areas of built-up extension. The identified ground units consist of six soil and five rock types. Soil units comprise one fill formation of variable composition and consistency with a ranging thickness between 2 m and 6 m and five loose to cohesive deposits, Holocene to Upper Pliocene in age, with high variation in grain size, density and plasticity factors. Rock lithologies range from highly to moderately weathered, closely fractured serpentinites and schists to fresh, widely fractured limestones. The old city of Kastoria is founded mainly on stable rocky ground and does not show any remarkable geotechnical problems. However, the need of built-up extension however and improvement of infrastructures, led to configurations of the marshy areas and to the use of foundation ground with poor mechanical properties, which locally need a special treatment to become stable.